Periodontal Health Status of Patients attending Isra Dental College OPD using CPI Index (Medical Forum Monthly, 2024)
Objectives: To assess the periodontal health status among patients attending Dental OPD of Isra dental college Isra University Hyderabad. To predict for planning of periodontal care programmes for population attending Dental OPD of Isra dental college Isra University Hyderabad.Study Design: Cross sectional study.Place and Duration of Study: This study was carried out in dental OPD of Isra dental college Isra University Hyderabad. Duration of study was six months.Materials and Methods: The study was conducted on 500 subjects. For the assessment of the periodontal status of a population visiting OPD of Isra Dental College, CPITN recording were made for patients visiting within 6 months and selected at random without consideration of sex, religion, education, socioeconomic condition and systemic health at filtration clinic of OPD. The subjects were examined by a single examiner with the help of a plane mouth mirror and CPITN Probe. The index teeth were selected for examination.Results: A total of 500 subjects were surveyed in the study who visited filtration clinic of Dental opd of Isra dental college out of them 190 (38%) were female and 310 (62%) were males (fig 1). (Fig.2) showed the percentage of CPITN code 1 was highest (54.8%) which shows bleeding gums, followed by the percentage of code 2 (27.2%) which represents the presence of supra and sub gingival calculus. The percentage of code 3 was found to be 8% denoted by presence of periodontitis having pathological pocket depth of 4 to 5 mm. About 10 % patients were found having healthy periodontal tissues.Conclusion: Using the research results, a greater effort can be made in providing periodontal health to the population of at or around the city of Hyderabad. Systemic diseases and environmental or genetic risk factors were not included in this study. A further broad scale study is needed to measure an accurate prevalence of periodontal diseases among the patients of at or around city of Hyderabad